2008
DOI: 10.1210/jc.2008-0962
|View full text |Cite
|
Sign up to set email alerts
|

Change of Serum Antithyroglobulin Antibody Levels Is Useful for Prediction of Clinical Recurrence in Thyroglobulin-Negative Patients with Differentiated Thyroid Carcinoma

Abstract: Serum TgAb levels measured at 6-12 months after remnant ablation could predict recurrence in patients with undetectable Tg values. In patients with undetectable Tg and positive TgAb values, a change in TgAb concentration during the early postoperative period may be a prognostic indicator of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
148
3
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 20 publications
19
148
3
10
Order By: Relevance
“…Although undetectable pre-ablation Tg levels usually indicate complete previous surgery, our data reinforce earlier observations that, in a low percentage of patients, this situation may be related to non-detectable Tg or to the presence of TgAb (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)31). We believe that, when concurrent chronic thyroiditis is found by the pathologist, or when initial TNM stages are diswith DTC, compared with the 10% generally seen in the general population (20).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although undetectable pre-ablation Tg levels usually indicate complete previous surgery, our data reinforce earlier observations that, in a low percentage of patients, this situation may be related to non-detectable Tg or to the presence of TgAb (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)31). We believe that, when concurrent chronic thyroiditis is found by the pathologist, or when initial TNM stages are diswith DTC, compared with the 10% generally seen in the general population (20).…”
Section: Discussionsupporting
confidence: 89%
“…found that less than 1% of patients who became TgAb-negative or displayed more than 50% decrease in TgAb levels over the 6 to 12 months period after radioiodine treatment had recurrence detected during follow-up. In contrast, 19% of patients in whom TgAb decreased less than 50%, as well as the 37% in whom TgAb concentrations rose, were diagnosed with recurrence (29).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The trend of anti-TgAb levels over time (9)(10)(11)(12) and serial imaging based on the extent of disease (13,14) are generally recommended for monitoring these patients. Measurement of Tg-LC/MS has been developed as a method to provide an accurate level of Tg, avoiding the interference of these antibodies, and over the past few years, it has been adopted by several commercial laboratories.…”
Section: Discussionmentioning
confidence: 99%